Partial molecular characterization of different proviral strains of bovine leukemia virus - Juliarena, Marcela A. (2012)
Bovine leukemia virus (BLV)-infected cattle were classified by their proviral load into low and high proviral load profiles (LPL and HPL, respectively). Blood from these animals was used to infect sheep to obtain multiple identical copies of integrated provirus. An env fragment of BLV was amplified from all infected sheep and sequenced. The sequences that were obtained were compared to already published BLV genome sequence, resulting in three clusters. Mutations could not be attributed to the passage of provirus from cattle to sheep and subsequent amplification and sequencing. The description of two different proviral load profiles, the association of the BoLA-DRB3.2 0902 allele with the LPL profile, the availability of complete BLV sequences, and the comparison of a variable region of the env gene from carefully characterized cattle are still not enough to explain the presence of animals in every herd that are resistant to BLV dissemination.